KURIKULUM KESENIAN PASCA GEMPA SD/MI DI DAERAH ISTIMEWA YOGYAKARTA - Wiharsih, Rumi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
The curriculum applied in the earthquake areas is that which is adjusted to the present situation and condition. Physically and psychologically, the human resources will be different from the normal situation before the earthquake happened. The curriculum that is specially designed to recover the post-earthquake condition is called post-earthquake or emergency curriculum. This curriculum will be implemented temporarily to support the main curriculum that has been applied in the previous normal situation and condition. The curriculum is designed using post-earthquake psychological-social approach. The aims are formulated to create fun teaching-learning situation in class and to eradicate the students' trauma caused by the earthquake. Key words: curriculum, earthquake victims and psycho-social approach